Citrullinated IGF2BP1 promotes rheumatoid synovial aggression via increasing the mRNA stability of SEMA3D - Yang Qin; Li Liu; Yanwen Zhang; Xiaowei Chen; Jiani Zhang; Sunwang Ling; Jianguang Wang; Xinyu Yang (Communications Biology)
Abstract Protein citrullination modification plays a pivotal role in the pathogenesis of rheumatoid arthritis (RA), and anti-citrullinated protein antibodies (ACPAs) are extensively employed for clinical diagnosis of RA. However, there remains limited understanding regarding specific citrullinated proteins and their implications in the progression of RA. In this study, we screen and verify insulin-like growth factor-2 mRNA binding protein 1 (IGF2BP1) as a novel citrullinated protein with significantly elevated citrullinated level in RA. Autoantibodies against citrullinated IGF2BP1 are further detected in serum and synovial fluid samples from RA patients, which are positively correlated with erythrocyte sedimentation rate (ESR) and disease activity score 28 (DAS28). Transcriptomic sequencing and functional verification show that citrullination at the R167 site of IGF2BP1 promotes the proliferation, migration, and invasion of RA fibroblast-like synoviocytes (RA-FLSs) by improving the mRNA stability of Semaphorin 3D (SEMA3D). Experiments in collagen-induced arthritis (CIA) mice, the classical animal model of RA, show that IGF2BP1 R176K point mutation (Igf2bp1 R167K/R167K) mice exert reduced inflammatory response, clinical scores, and joint destruction. At a molecular level, citrullination of IGF2BP1 promotes the stability of SEMA3D mRNA by promoting the interaction between IGF2BP1 and its cofactor ELAV-like protein 1 (ELAVL1), thereby promoting the invasiveness of RA-FLSs. In this study, a new citrullinated protein of IGF2BP1 is discovered, and the molecular mechanism of its citrullinated modification promoting the progression of RA disease is elucidated, which provides theoretical basis for the diagnosis and treatment of RA.